Surface roughness of denture base and reline materials after disinfection by immersion in chlorhexidine or microwave irradiation - Machado, Ana Lucia [UNESP]; Giampaolo, Eunice Teresinha [UNESP]; Pavarina, Ana Claudia [UNESP]; Jorge, Janaina Habib [UNESP]; Vergani, Carlos Eduardo [UNESP] (Wiley-Blackwell, 2012)
Background: This study evaluated the effect of disinfection by immersion and microwave irradiation on the roughness of one denture base resin (Lucitone-L) and five relining materials, three hard (Tokuyama Rebase II-TR, New Truliner-NT, Ufigel Hard-UH) and two resilient (Trusoft-T, Sofreliner-S).Methods: Fifty specimens were made and divided into groups: CL2 specimens were brushed with 4% chlorhexidine (1 min), immersed in the same solution (10 min) and immersed in water (3 min); MW2 specimens were immersed in water and microwave irradiated (650W; 6 min); CL2 and MW2 specimens were disinfected twice; CL7 and MW7 specimens were submitted to seven cycles using chlorhexidine or microwave irradiation, respectively; W specimens were not disinfected and remained in water (37 degrees C; 7 days).Results: Results were statistically analysed (p = 0.05) and revealed that, at baseline, the highest mean value was observed for T (p < 0.001). Material NT showed increase in roughness after the first (p = 0.003), second (p = 0.001), seventh (p = 0.000) cycles of microwave disinfection and after 7 days of immersion in water (p = 0.033).Conclusions: Resilient liner S presented significant increase in roughness after the second cycle of disinfection with chlorhexidine (p = 0.003). Material T exhibited significantly decreased roughness in group W (p = 0.010), while microwaving produced severe alterations on its surface.
Keywords: chemical compounds; denture bases; denture rebasing; microwaves; surface properties